Utilization of Dry Battery Waste Carbon Rod for Whiteboard Marker Ink - Wulandari, Retno; Zulfa, Nabila Qothrunnada; Afifah, Muanda; Andini, Evita Tri (Green Publisher, 2025)
Disposable batteries are commonly found in dry batteries (or zinc-carbon batteries) that are discarded and converted into waste. Zinc-carbon batteries have a physical component, a carbon rod that has a graphitic carbon component that has a black pigment. This black pigment is utilized as an alternative black carbon material for the manufacture of whiteboard marker ink. This research aims to utilize graphite carbon from waste batteries as a pigment in whiteboard marker ink and test the formulation of ink samples. The supporting materials in this research are glycerin, thinner, gum arabic solution, and emulsion. The best ink sample has a density value of 1.35 g/cm3, a viscosity of 0.13 Poise, a transmittance of 72 lux, a pH of 7.67, adhesion has a dense wet nature and moderate absorbency, and non-volatility of 75% ink using a carbon mass of 6.5 grams and the ratio of thinner and glycerin is 2:5.